Heavy Weight Protein Affected by Lead Acetate in Bactrocera dorsalis - Rizwanul Haq; M. Farhanullah Khan; Ehteshamul Haq (Journal of Basic & Applied Sciences, 2012)
The studies were carried out on toxic effects of lead acetate, which could contaminate the environment, such as food, water, air and soil, therefore insects could be influenced easily by the lead., Bactrocera dorsalis was studied at 48 hours post treatment, under the effects of lead acetate, in different concentrations. It was observed that, under the effects of lead abnormalities, and deformity were developed in the larvae of flies. Thus these flies could present a useful module for the quick transmission of the environmental hazards of lead, which exerts a specific physiological and morphological effect on their bodies.